2019
DOI: 10.1088/1757-899x/594/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Speed Control of DC Motor Using Chopper Based on Fuzzy Logic

Abstract: This paper present the speed control of DC Motor based on boost converter under the controlling of fuzzy logic. The DC motor has armature and field winding in which armature winding is controlled by using boost converter which is triggered by fuzzy logic controller which consist of 7x7 rule and the input are change in error and rate of change of error and output is firing angle. The fuzzy logic controller gives smooth, reliable, efficient speed controlling of DC motor. Further the compative analysis between fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In addition, fuzzy controller was more complicated controller but with a good and more stable performance. Singh et al [17] presented DC motor speed control based on boost converter with fuzzy logic control. They observed that the performance parameter of the system showed better transient and steady state performance using the fuzzy logic controller.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fuzzy controller was more complicated controller but with a good and more stable performance. Singh et al [17] presented DC motor speed control based on boost converter with fuzzy logic control. They observed that the performance parameter of the system showed better transient and steady state performance using the fuzzy logic controller.…”
Section: Introductionmentioning
confidence: 99%